Development of a Web-Based Patient Service Management Information System to Improve Administrative Efficiency at Su'adah Clinic, Palembang - Syahabiah, Syahabiah (Journal of Health Innovation and Environmental Education, 2026)
Purpose of the study: This study aimed to develop and evaluate a web-based patient service management information system to improve administrative efficiency at Su’adah Clinic in Palembang.Methodology: This research employed a research and development approach using the Waterfall system development model. Problem identification was conducted using the PIECES framework (Performance, Information, Economy, Control, Efficiency, and Service). Data were collected through observation, interviews, and documentation analysis at the clinic. The developed system integrates patient registration, administrative data management, payment processing, and automated reporting into a single web-based platform.Main Findings: The implementation of the developed system significantly improved administrative performance at the clinic. The average patient registration time decreased from approximately 10 minutes to 3 minutes, while average patient waiting time was reduced from 25 minutes to 10 minutes. The time required to retrieve patient records decreased from 5–7 minutes to less than 1 minute, and the preparation of monthly administrative reports was reduced from 2–3 hours to approximately 15 minutes. In addition, daily paper usage decreased from about 120 sheets to around 30 sheets after system implementation. User evaluation results indicated high acceptance of the system, with an overall satisfaction score of 4.5 out of 5.Novelty/Originality of this study: The novelty of this study lies in the development of an integrated web-based patient service management system specifically designed for small-scale healthcare clinics, combining online patient registration, administrative management, payment documentation, and automated reporting within a single accessible platform.